Cool PDO phase leads to recent rebound in coastal southern California fog - Witiw, Michael R.; LaDochy, Steve (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
The relationship between coastal fog in southern California and the Pacific Decadal Oscillation (PDO) is investigated during the last decade. Fog occurrence was examined at two locations in southern California: San Diego and Los Angeles international airports. Both locations are located near the Pacific coast with strong marine influences. The period looked at was 2001 through 2012. The cool season (October-March) and warm season (April-September) were examined separately because of the different types of fog that prevail in each season. Previous studies have shown a relation between fog and the Pacific Decadal Oscillation (PDO). However, a switch in polarity in the PDO in the mid-1970s (from a cool to a warm phase) coupled with a sharp decrease in particulate concentrations calls into question the strong relationship shown. Further studies suggest that the decrease in dense fog seen from the 1960s through the 1990s was largely due to increasing urban heat island effects coupled with a decrease in atmospheric particulate matter. Since 1998, the PDO again changed polarity and fog frequencies began to rise. However, urban heat island and particulate effects were relatively constant making it easier to isolate any effects of the PDO on fog occurrence. Previous studies examined the occurrence of dense fog (visibility less than 400 meters), but because of the decrease in fog in this category, 800 meters was chosen this time. That also corresponds to the 0.5 mile visibility which triggers special reports at the California airports when visibility moves through this threshold. Although there was no strong relationship between fog and PDO in the most recent period, Pacific Ocean oscillations were found to show significant relationships with fog frequencies historically. Upwelling indices show a significant relationship with fog frequencies when examined by the phase of the PDO. Even stronger relationships are found when selecting La Niña and El Niño events.